2022
DOI: 10.51847/zof4tcfekt
|View full text |Cite
|
Sign up to set email alerts
|

Natural polymer Effect on gelation and rheology of ketotifen-loaded pH-sensitive in situ ocular gel (Carbapol) ‎

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…To assure therapeutic outcomes, immunosuppressant drugs are typically administered via conventional techniques that frequently demand high doses of the drugs, although this can lead to harmful side effects such as infections, cancers, and specific side effects in pregnancy [ 81 , 82 ]. Synthesis of formulations using XG carrying the optimum amount of drug to be effective at the target site was achieved by Sadeq et al [ 83 ]. Ketotifen fumarate is an antihistamine (selectively blocks histamine H1 receptors) and is used in conjunctivitis and rhinitis.…”
Section: Xg-based Systems For the Delivery Of Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assure therapeutic outcomes, immunosuppressant drugs are typically administered via conventional techniques that frequently demand high doses of the drugs, although this can lead to harmful side effects such as infections, cancers, and specific side effects in pregnancy [ 81 , 82 ]. Synthesis of formulations using XG carrying the optimum amount of drug to be effective at the target site was achieved by Sadeq et al [ 83 ]. Ketotifen fumarate is an antihistamine (selectively blocks histamine H1 receptors) and is used in conjunctivitis and rhinitis.…”
Section: Xg-based Systems For the Delivery Of Drugsmentioning
confidence: 99%
“…Amongst the optimised formulations, formulation with 0.75% Carbopol and 0.3% XG was found to be optimum. It had a drug encapsulation efficiency of 99.74%, gel-forming strength in 46.6 s, and drug release of up to 8 h [ 83 ]. These findings demonstrate the impact of polymer combinations; it was observed that as XG or gellan gum concentrations rose, the percentage of the drug release reduced.…”
Section: Xg-based Systems For the Delivery Of Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…For gel, samples were sheared using spindle R6 at 10, 12, 20, 30, 50, 60, 100, 200 rpm. Utilizing plots of shear stress (rpm) vs viscosity (cP), the interpretation of rheological behavior was determined (23) .…”
Section: Determination Of Viscositymentioning
confidence: 99%
“…1 The recurrent incidence of severe nausea, poor gastrointestinal (GI) absorption, or vomiting in migraineurs makes it more difficult to administer oral medications. [2][3][4][5][6][7] The intranasal approach is easy for the individual to use, painless, free from sterility restrictions, and noninvasive; it improves medication intake uniformity and speed while avoiding issues with self-injections and is created to address the shortcomings of the oral route. 8 Although several good migraine treatments have been created utilizing nasal delivery, most have not been proven commercially viable.…”
Section: Introductionmentioning
confidence: 99%